Screening for Neurodevelopmental Impairments among less than 2 Years Old Children in a Tertiary Care Hospital in Dhaka city (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Neurodevelopmental impairment is an important issue in the context of normal growth of the children.Objective: The purpose of the present study was to find out the magnitude of neurodevelopmental impairments (NDIs) in young children in a tertiary care hospital Methodology: This cross sectional study was conducted in the Department of Paediatrics at Dhaka Medical College Hospital (DMCH) from January 2010 to June 2010 for a period of six months. All children with the age of 0 to 2 years irrespective of sex attended at the study place were selected as study population. Children getting developmental therapy, physiotherapy and anticonvulsant or muscle relaxant were excluded from this study. Development Screening Questionnaire (DSQ) was administered to mothers of children from birth to less than two years of age to assess their childs neurodevelopment. Then again neurodevelopmental assessment was done using a validated Rapid Neurodevelopmental Assessment (RNDA) method of evaluations of all children with positive screening results. RNDA was administered to identify the type of impairments and grades of severity. Items are arranged under the developmental parameters like gross motor, fine motor, vision, hearing, speech, cognition, behavior, and seizures for all age groups and for the age 0 to 1 month, additional primitive reflexes are examined along with other parameters.Result: Among 234 cases NDIs positive was found in 20(8.5%) cases. Among 20 children 16 (80%) were affected by cognitive impairment, 12 (60%) of each were affected by gross motor and behavioral impairment; 11 (55%) were affected by fine motor, 10(50%) speech, 8(40%) hearing, 7 (35%) visual impairment and 7 (35%) had seizure disorder.Conclusion: In conclusion NDIs are present in the general population of the Bangladesh with a very significant rate of which cognition is the most frequently involved and affected domain.Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 57-61